Excess LINC complexes impair brain morphogenesis in a mouse model of recessive TOR1A disease. (18th April 2018) - Dominguez Gonzalez, Beatriz; Billion, Karolien; Rous, Stef; Pavie, Benjamin; Lange, Christian; Goodchild, Rose
Abstract: Heterozygosity for the TOR1A -Δgag mutation causes semi-penetrant childhood-onset dystonia (OMIM #128100). More recently, homozygous TOR1A mutations were shown to cause severe neurological dysfunction in infants. However, there is little known about the recessive cases, including whether existing reports define the full spectrum of recessive TOR1A disease. Here we describe abnormal brain morphogenesis in ∼30% of Tor1a −/− mouse embryos while, in contrast, this is not found in Tor1a Δgag / Δgag mice. The abnormal Tor1a −/− brains contain excess neural tissue, as well as proliferative zone cytoarchitectural defects related to radial glial cell polarity and cytoskeletal organization. In cultured cells torsinA effects the linker of nucleoskeleton and cytoskeleton (LINC) complex that couples the nucleus and cytoskeleton. Here we identify that torsinA loss elevates LINC complex levels in the proliferative zone, and that genetic reduction of LINC complexes prevents abnormal brain morphogenesis in Tor1a −/− embryos. These data show that Tor1a affects radial glial cells via a LINC complex mediated mechanism. They also predict human TOR1A disease will include incompletely penetrant defects in embryonic brain morphogenesis in cases where mutations ablate TOR1A function.